Optimization of Screening Media to Improve Antimicrobial Biodiscovery from Soils in Undergraduate/Citizen Science Research-Engaged Initiatives - Leah McPhillips; John O'Callaghan; Carmel Shortiss; Stephen A. Jackson; Niall D. O'Leary (MDPI AG, 2024)
Background/Objectives: Research-engaged academic institutions offer the opportunity to couple undergraduate education/citizen science projects with antimicrobial biodiscovery research. Several initiatives reflecting this ethos have been reported internationally (e.g., Small World, Tiny Earth, MicroMundo, Antibiotics Unearthed). These programs target soil habitats due to their high microbial diversity and promote initial screening with non-selective, nutrient media such as tryptic soy agar (TSA). However, evaluation of published outputs to date indicates that isolate recovery on TSA is consistently dominated by the genera Bacillus, Pseudomonas, and Paenibacillus. In this study, we evaluated the potential of soil extract agar to enhance soil isolate diversity and antibiosis induction outcomes in our undergraduate Antibiotics Unearthed research program. Methods: We comparatively screened 229 isolates from woodland and garden soil samples on both tryptic soy agar (TSA) and soil extract agar (SEA) for antimicrobial activity against a panel of clinically relevant microbial pathogens. Results: On one or both media, 15 isolates were found to produce zones of clearing against respective pathogens. 16S rRNA gene sequencing linked the isolates with three genera: Streptomyces (7), Paenibacillus (6), and Pseudomonas (2). Six of the Streptomyces isolates and one Pseudomonas demonstrated antimicrobial activity when screened on SEA, with no activity on TSA. Furthermore, incorporation of the known secondary metabolite inducer N acetyl-glucosamine (20 mM) into SEA media altered the pathogen inhibition profiles of 14 isolates and resulted in broad-spectrum activity of one Streptomyces isolate, not observed on SEA alone. In conclusion, SEA was found to expand the diversity of culturable isolates from soil and specifically enhanced the recovery of members of the genus Streptomyces. SEA was also found to be a superior media for antibiosis induction among Streptomyces isolates when compared to TSA. It was noted that Paenibacillus isolates' antibiosis induction demonstrated a strain-specific response with respect to the growth media used. Conclusions: The authors propose SEA inclusion of in soil screening protocols as a cost-effective, complementary strategy to greatly enhance outcomes in undergraduate/citizen science-engaged antimicrobial biodiscovery initiatives.